Transformaciones en las prácticas educativas en contextos de COVID-19. Percepciones de un grupo de docentes argentinos - Elisondo, Romina Cecilia (Universidad de Costa Rica, 2021)
In the context of a global emergency and suspension of face-to-face activities in educational institutions, the objective of the study is to analyze changes in teaching practices at different times of isolation and social distancing due to COVID-19. A qualitative phenomenological study was carried out in order to understand meanings and meanings about educational practices. The study was carried out between August and September 2020, continuing a previous investigation that was carried out in the first moments of social isolation. Thirty teachers residing in the Department of Río Cuarto (Argentina) participated in the present study. All the people participating in the study are women. The sampling was intentional and by opportunity. For data collection, it will be used in questionnaires with open-choice questions and semi-structured interviews. Triangulation and communicative validation processes were carried out. From the qualitative analysis with ATLAS.ti (segmentation, construction of citations, coding, creation of memos, categorization and theorization), five general categories were constructed to systematize the data: Trencadís educational in quarantine; Deep gaps and inequalities; Teaching overload and collaborative work Specificities of the proposals according to educational levels and Unexpected learning. The results indicate that teachers have created various educational proposals, using different mediations and generating changes in practices. The participants perceive overload in their activities and educational inequalities. The analyzes also show specificities according to levels and unexpected learning in teachers and students. From the theories of creativity, it is observed that many of the related pedagogical proposals include components that have been defined as creative teaching and learning contexts. Thinking about augmented and multimodal education, which integrates different communicative practices, is interesting to move into the new normalities. The particularities of creative contexts may be relevant to discuss future multimodal educational environments. Likewise, it is considered essential to revalue the educational experiences built in a pandemic and to recognize the value of the work done by teachers, students and families.